2008
DOI: 10.2478/v10042-008-0022-7
|View full text |Cite
|
Sign up to set email alerts
|

ZAP-70 and CD38 expression are independent prognostic factors in patients with B-cell chronic lymphocytic leukaemia and combined analysis improves their predictive value.

Abstract: Abstract:Recently identified biological risk factors in B-cell chronic lymphocytic leukemia (B-CLL) include ZAP-70 and CD38 expression. The present study was conducted to clarify whether a combined analysis could improve predictive impact of these two parameters. We examined the expression of ZAP-70 and CD38 by flow cytometry method in 217 newly diagnosed, consecutive, unselected and well characterized B-CLL patients in relation to laboratory parameters and clinical outcome. We confirmed that both ZAP-70 as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have reported that a combination of CD38 and ZAP-70 is the best predictor of disease progression. 3335 Using the Spearman’s correlation, we found that both CD45RA + T reg and CD8 T reg were significantly inversely correlated with combined CD38 and ZAP-70 expression (Spearman’s r = −0.55 ( P = 0.02) and Spearman’s r = −0.58 ( P = 0.01), respectively). Using the Mann–Whitney test, we compared the mean of these two populations in two groups CD38 − /ZAP70 − and CD38 + /ZAP70 + , and it was found that the frequency of CD45RA + T regs and CD8 + T regs was significantly different.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that a combination of CD38 and ZAP-70 is the best predictor of disease progression. 3335 Using the Spearman’s correlation, we found that both CD45RA + T reg and CD8 T reg were significantly inversely correlated with combined CD38 and ZAP-70 expression (Spearman’s r = −0.55 ( P = 0.02) and Spearman’s r = −0.58 ( P = 0.01), respectively). Using the Mann–Whitney test, we compared the mean of these two populations in two groups CD38 − /ZAP70 − and CD38 + /ZAP70 + , and it was found that the frequency of CD45RA + T regs and CD8 + T regs was significantly different.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25][26] Although ZAP70 has been shown as an independent prognosis parameter in many studies, there are controversies for CD38. 27 As it has been suggested by Moreno et al the correlation of IgVH mutations, ZAP70 and CD38 expression with response is unclear and needs further investigation. 28 Besides many studies which have supported the prognostic significance of those markers, there is considerable number of controversial comments as well.…”
Section: Discussionmentioning
confidence: 96%
“…Deletions of 13q14.3, 11q23, and 6q12 and trisomy 12 are common abnormalities associated with CLL. 9 – 11 It has been proven that in patients with deletion of 13q14.3, miR15a and miR16–1 expression is inhibited or at very low levels. MiR15a expression reduced in 25% of patients with CLL, and low expression of miR16-1 reported in 45% of cases.…”
Section: Microrna Expression In Chronic Lymphocytic Leukemiamentioning
confidence: 99%